B Lymphocytes Are a Predictive Marker of Eribulin Response and Overall Survival in Locally Advanced or Metastatic Breast Cancer: A Multicenter, Two-Cohort, Non-Randomized, Open-Label, Retrospective Study - Tashireva, Liubov A.; Popova, Nataliya O.; Kalinchuk, Anna Yu.; Goldberg, Viktor E.; Kovalenko, Elena I.; Artamonova, Elena V.; Manikhas, Aleksey G.; Ponomarenko, Dmitriy M.; Levchenko, Nataliya V.; Rossokha, Elena I.; Krasilnikova, Svetlana Yu.; Zafirova, Marina A.; et al. (Frontiers in Oncology, 2022)
Triple-negative breast cancer has no specific treatment and unfavorable prognosis. Eribulin is a one of the drugs widely used in this cohort of this patients. In addition to its antimitotic effect eribulin has an immunomodulant effect on the tumor microenvironment. In this study we discover immunological markers with the ability to predict benefit from eribulin within locally advanced or metastatic triple-negative breast cancer. Primary objective was to explore the association of composition of immune cell in microenvironment with response to eribulin. Key secondary objective was overall survival. Seven-color multiplex immunofluorescence were used to phenotyping lymphocytes in primary tumor. It has been shown that PD1-negative-to-PD1-positive B cells ratio in primary tumor more than 3 is an independent predictor of the short-term effectiveness of eribulin (OR (95%CI) 14.09 (1.29-153.35), p=0.0029) and worse overall survival (HR (95%CI) 11.25 (1.37-70.25), p=0.0009) in patients with locally advanced or metastatic triple-negative breast cancer.